(untitled) (Collection of scientific works «Modern structures of metal and wood», 2022)
The paper demonstrates the applications of the hysteresis envelope model on the example of a double extended end plate beam-to-column bolted joint. The hysteresis envelope model represents a new analytical trilinear model that can describe the cyclic behaviour of joints in a moment-resisting steel frame and is suitable for nonlinear static pushover analysis. The principle of determining the parameters of the hysteresis model is based on the monotonic curve of joint, which can be determined by applying the Component method using commercial software for the joint design. After trilinear idealisation of nonlinear − curve, the parameters of the hysteresis envelope model are then obtained by multiplying the parameters of the monotonic model with a nonlinear exponential function. Predicting the cyclic behaviour of the joint using the hysteresis envelope model is satisfactory for further practical application.